Innovation Management Strategies of Four Pioneering Entrepinays from Camarines Sur, Philippines - Caning, Ma. Cresilda Martinez; Edralin, PhD, Divina M (ABAC ODI JOURNAL Vision. Action. Outcome, 2016)
In this study, we investigated the case of four pioneering Filipina entrepreneurs from Camarines Sur who managed to survive the initial risks associated with start-ups to become one of the market leaders in their respective industries. Camarines Sur is one of the least developed provinces in the Philippines but rich in human and natural resources. Given this background, our study examined the innovation management practices of four women entrepreneurs engaged in agrotourism, trading, and food business in the province. Our study determined and compared the degree by which these entrepreneurs implement practices along the seven innovation management areas. The framework posited by Adams, Bessant, and Phelps (2006) on measure of innovation management was used. Their model consists of seven categories, namely: inputs, knowledge management, strategy, organization and culture, portfolio management, project management and commercialization. Innovation as an output and as a process is the result of novel combinations created by the entrepreneur (Schumpeter, 1934). Based on the content analysis of the interview data, our results revealed that the four Filipina entrepreneurs rated high on the following innovation management measures: innovation strategy, organization and culture. Innovation strategy is manifested in their vision, commitment to innovation and leadership while their efforts to motivate their people, propensity to take risks and efforts to make the organization an attractive place to work on points to the value they put on the measure “organization and culture.” We proposed that successful entrepreneurs like these Filipinas, should have succession plans to ensure the continuity of their innovative management practices. Keywords: innovation management, innovation, entrepreneurship, Filipina entrepreneurs